z=(3^24÷3^12-2^13×2^16-5^3^0)÷[(3^6)^2-2^29^1-5^2^0] Rezolvati ecuatia : 4(x+2)=2x+18
Răspunsuri la întrebare
Răspuns de
0
Z=(3^24÷3^12-2^13×2^16-5^3^0)÷[(3^6)^2-2^29^1-5^2^0] =
=(3^12-2^29-5^1)÷(3^12-2^29-5^1) =1
4(x+2)=2x+18
4x+8=2x+18
2x=10
x=5
=(3^12-2^29-5^1)÷(3^12-2^29-5^1) =1
4(x+2)=2x+18
4x+8=2x+18
2x=10
x=5
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă